Organizational laxity of middle and secondary school principals in the Dhi Qar Education Directorate and its impact on the professional affiliation of physical education teachers from their point of view - Reja, Thamer (Journal of Physical Education, 2025)
The current study aimed to know the reality of organizational laxity among school principals and its reflection on physical education teachers and the correlation between them, on a sample of physical education teachers in middle and preparatory schools affiliated with the Dhi Qar Education Directorate, numbering (200) teachers, who were randomly distributed into three samples (exploratory experiment (14), construction (123), application (63)), using the descriptive analytical approach and correlational relationships, through building and applying the organizational laxity scale consisting of three areas (laziness at work, alienation commitment, job frustration) distributed over (19) phrases, and the professional affiliation scale consisting of three areas (professional loyalty, continuity at work, job commitment) distributed over (17) phrases, and the results were processed through the statistical system (spss), and the most important conclusions were that the existence of organizational laxity among school principals shows limited practices that weaken administrative support for sports activities, which contributes to accumulations that affect the sustainability of the effective application of the sports curriculum. School principals’ greater emphasis on academics than on sports indicates lax administrative control over coordination and the full implementation of educational curricula throughout the school year. The study recommended that administrative oversight be activated by the Educational Supervision Directorate to continuously monitor physical education lessons. School principals should also pay attention to the psychological and professional conditions of physical education teachers to maintain their commitment to their profession.